Identification and characterization of the lactic acid bacteria isolated from Malaysian fermented fish (Pekasam) - Md Yasin, Ida Muryany; Md Yasin, Ina Salwany; Ghazali, A. R.; Hing, Hiang Lian; Rajab, Nor Fadilah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Recently researchers are interested with the biotherapeutic potential of probiotics in gut disease treatment. The bacteria are generally regarded as a safe, have a stability of usage and originate from the natural resources. The study aims to identify and characterize the potential probiotic Lactic Acid Bacteria (LAB) isolated from Malaysian fermented fish product known as Pekasam. Fourty isolates obtained were firstly screened for their antagonism activities against the common pathogenic bacteria; Esherichia coli, Staphylococcus aureus and Klebsiella sp. Our study revealed only three (labeled as L8, L20 and S1) of the isolates tested showed broad antimicrobial effects towards the pathogenic bacteria. All of the isolates were also γ-hemolytic and tolerant to various pH (pH 3, 5 and 7.5) and 0.3% (w/v) bile salts. The bacteria isolates of strain L8 and L20 were susceptible to seven antibiotics tested except vancomycin and tetracycline whereas S1 was resistant to all antibiotics. Phenotypic tests revealed that both bacteria isolates of strain L8 and L20 were Bacillus megaterium while S1 was Pediococcus pentosaceus whereas 16S rRNA gene sequence analysis showed potential bacteria isolates of strain L8 and L20 belonged to the Lactobacillus plantarum (99% similarity) and S1 was characterized as Lactobacillus pentosus (100% similarity) respectively. Our present study showed that the probiotics of strain L8, L20 and S1 isolated from the fermented fish (Pekasam) exhibited the potential probiotic properties to be developed as biotherapeutic agents.